3D finite element modelling of drilling: The effect of modelling method. (November 2021) - Priest, Joshua; Ghadbeigi, Hassan; Avar-Soberanis, Sabino; Gerardis, Stefanos
Abstract: A comprehensive benchmarking study has been carried out to determine the influence of the mesh formulation and chip separation methods on the reliability and accuracy of finite element modelling of large diameter drilling operations. The Coupled Eulerian–Lagrangian and the updated-Lagrangian (with element deletion) formulations available in ABAQUS/Explicit, together with the updated-Lagrangian (with re-meshing) formulation in DEFORM 3D are compared by simulating through-coolant drilling of AISI 1045. The Johnson–Cook damage model was implemented by a sub-routine in DEFORM 3D to ensure a consistent damage model is implemented across the formulations. Experimentally measured drilling thrust force, torque, and chip thickness values were used to compare the models performance and assess the accuracy of the predictions. The updated-Lagrangian with dynamic re-meshing was found to be the best performing methodology concerning the accuracy of predictions, whilst the Coupled Eulerian–Lagrangian methodology significantly under-predicted the drilling thrust force and torque. Due to numerical instabilities and computational cost, the updated-Lagrangian with element deletion method is not recommended to model large diameter drilling.